First‐food systems transformations and the ultra‐processing of infant and young child diets: The determinants, dynamics and consequences of the global rise in commercial milk formula consumption. Issue 2 (3rd November 2020) - Baker, Phillip; Santos, Thiago; Neves, Paulo Augusto; Machado, Priscila; Smith, Julie; Piwoz, Ellen; Barros, Aluisio J. D.; Victora, Cesar G.; McCoy, David
Abstract: The inappropriate marketing and aggressive promotion of breastmilk substitutes (BMS) undermines breastfeeding and harms child and maternal health in all country contexts. Although a global milk formula 'sales boom' is reportedly underway, few studies have investigated its dynamics and determinants. This study takes two steps. First, it describes trends and patterns in global formula sales volumes (apparent consumption), by country income and region. Data are reported for 77 countries, for the years 2005–19, and for the standard (0–6 months), follow‐up (7‐12 m), toddler (13‐36 m), and special (0‐6 m) categories. Second, it draws from the literature to understand how transformations underway in first‐food systems – those that provision foods for children aged 0–36 months – explain the global transition to higher formula diets. Total world formula sales grew by 115% between 2005 and 2019, from 3.5 to 7.4 kg/child, led by highly‐populated middle‐income countries. Growth was rapid in South East and East Asia, especially in China, which now accounts for one third of world sales. This transition is linked with factors that generate demand for BMS, including rising incomes, urbanisation, the changing nature of woman's work, social norms, media influences and medicalisation. It also reflects the globalization of the baby food industry and its supply chains, including the increasing intensity and sophistication of its marketing practices. Policy and regulatory frameworks designed to protect, promote and support breastfeeding are partially or completely inadequate in the majority of countries, hence supporting industry expansion over child nutrition. The results raise serious concern for global child and maternal health.